2008
DOI: 10.1007/s00198-008-0581-7
|View full text |Cite
|
Sign up to set email alerts
|

Signs of irreversible architectural changes occur early in the development of experimental osteoporosis as assessed by in vivo micro-CT

Abstract: Changes to the bone architecture and mechanics within twelve weeks after OVX highlight the importance of early diagnosis and treatment of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 31 publications
7
38
0
Order By: Relevance
“…Some authors report oestrogen deficiency leading to trabecular thickening while others describe thinning of Tb.Th in the tibia. 14,17,25 Although we also observed a significant decrease of Tb.Th in the sham animals, the values in the ovx group were significantly different compared with the control group at the time of the last scan 10 weeks postsurgery.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Some authors report oestrogen deficiency leading to trabecular thickening while others describe thinning of Tb.Th in the tibia. 14,17,25 Although we also observed a significant decrease of Tb.Th in the sham animals, the values in the ovx group were significantly different compared with the control group at the time of the last scan 10 weeks postsurgery.…”
Section: Discussionsupporting
confidence: 56%
“…16 We selected the proximal tibial metaphysis and the lumbar spine as the two skeletal sites for evaluation of morphological changes because they are often used in preclinical research for this purpose. 5,14,17 Moreover, it has been described only recently that they belong to the skeletal Data of each hind limb are shown as group means + SD (n ¼ 4). P values are reported for the one-way analysis of variance representing significant differences of the 20 mm measurement from the 41 mm scan in square brackets and significant differences between the ovx and the sham group-in curly brackets, Ã þP , 0.05 BV/TV: bone volume fraction; Conn.D: connectivity density; Tb.Sp: trabecular separation; Tb.N: trabecular number; Tb.Th: trabecular thickness Figure 4 Serum levels of type I collagen degradation fragments (RatLaps TM ) and osteocalcin 10 weeks after sham surgery and ovariectomy, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This time point has been remarked as the early time point when major degenerative bone changes were found. 28,42,43 Recently, a study has elucidated that after 4 weeks of OVX (only 2 weeks after the injection of ZOL was started), the OVX group has shown the loss of the bone volume fraction in 64 %, whereas the OVX+ZOL group has shown the bone volume fraction similarly to the baseline. 34 In our study, we started to apply orthodontic force 4 weeks after OVX and we found almost the same results of both orthodontic tooth movement and OIRR in OVX+ZOL and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Bony microstructure also has been assessed in animal studies by micro-CT (high-resolution peripheral quantitative computed tomography) [10,52,53]. Micro-CT has become increasingly popular for in vivo assessment of osteoporosis in human bone [8,9], and we presumed it could be used similarly with porous tantalum.…”
Section: Introductionmentioning
confidence: 99%